A new butenolide derivative from the deep-sea fungus Aspergillus terreus SCSIO FZQ028. Issue 14 (17th July 2020) - Zeng, Qi; Zhong, Wei-Mao; Chen, Yu-Chan; Xiang, Yao; Chen, Xia-Yu; Tian, Xin-Peng; Zhang, Wei-Min; Zhang, Si; Wang, Fa-Zuo
Abstract: A new butenolide derivative (±)-asperteretal F (1 ) and related congener (2 ) recently reported containing an unusual 2-benzyl-3-phenyl substituted lactone core, together with five known compounds (3 –7 ) were isolated and characterized from the fungus Aspergillus terreus . SCSIO FZQ028 derived from a deep-sea sediment of South China Sea. Their chemical structures were established on the basis of 1D- and 2D-NMR spectroscopic data, and HR-ESI-MS analysis. Additionally, all the compounds were evaluated for the antioxidative activities against DPPH, cytotoxic activities against two tumor cell lines (SF-268 and HepG-2), and antimicrobial activities. Compounds 2 -4, and 7 showed significant activities against DPPH with IC50 ranging from 5.89 to 10.07 μg/mL. Compounds 2 and 4 showed moderate antimicrobial activities against all four tested bacteria.